Pengaruh Kesehatan Kerja Dan Beban Kerja Terhadap Work Life Balance : Studi Kasus PT. Citra Mediatama Indonesia - Hanny Novita Ramadhan; Tungga Buana Irfana; Supriyanto Supriyanto; Djuni Thamrin; Matdio Siahaan (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
This research aims to determine and analyze the influence of occupational health and workload on work life balance at PT Citra Mediatama Indonesia. This type of research is quantitative and the data analysis used is classical assumption testing and multiple linear regression analysis, to test and prove the research hypothesis using the SPSS version 26 application. Partially, the occupational health variable has a significant influence on work life balance with the calculated t-value > t-table. Based on the test results and data analysis, partial test calculation results were obtained which showed a value of 9,536 (t-count) > 1,992 (t-table) with a significance value of 0.000 < 0.05. Partially, the workload variable has a significant influence on work life balance with a t-value < t-table. Based on the test results and data analysis, partial calculation results were obtained which showed a value of -6,418 (t-count) < 1,992 (t-table) with a significance value of 0.000 < 0.05. Meanwhile, based on the simultaneous test results obtained from this research, the occupational health and workload variables have obtained a value of 72,942 (calculated f) > 3.12 (table f).